The Waiter Servant in Later Roman Art - DUNBABIN, Katherine M. D. (American Journal of Philology, 2003)
Servants are present in banquet and bathing scenes. Some of them are visible on paintings (Philippopolis/Plovdiv, Themolica, Constanta, Sidon, Viminacium/Stari Kostolac, Rome, Ephesos) and mosaics (Apelles 2001-2004, E.M.M.)
p. 443-468, 25 ill. n.b.
Keywords: Iconographie; Bain (représentation); Banquet (scène de); Peinture murale; Serviteur (représentation); Bulgarie; Constanţa, Constanza; Éphèse; Italie; Kostolac; Liban; Plovdiv; Rome; Serbie; Sidon